Evaluating the role of nanoparticles in enhancing bone regeneration in dental implantology - K Sitamahalakshmi; Abhishek; P George Skariah; Reghunathan S Preethanath; Samiksha Dubey; Tazeen Dawood (Wolters Kluwer Medknow Publications, 2024)
Background: Dental implantology has witnessed substantial progress in recent years, driven by a growing emphasis on optimizing bone regeneration around dental implants. Nanoparticles have emerged as a potential tool for enhancing osseointegration and bone tissue regeneration. Materials and Methods: This human clinical trial enrolled 60 adult participants requiring dental implants. Patients were randomly assigned to one of two groups: a control group receiving conventional dental implants, and an experimental group receiving dental implants with nanoparticle-coated surfaces. Radiographic imaging, histological analysis of bone biopsies, and implant stability assessments were conducted at three and six months post-implantation. Results: Histological examination of bone biopsies revealed a statistically significant increase in new bone formation in the experimental group compared to the control group at both three and six months (P < 0.05). Radiographic assessment demonstrated a 25% higher bone density around nanoparticle-coated implants (P < 0.01) at the six-month mark. Implant stability quotient (ISQ) measurements indicated a 20% greater stability in the experimental group (P < 0.05) at the same time point. Conclusion: This human clinical trial provides strong evidence that the incorporation of nanoparticles on dental implant surfaces enhances bone regeneration and osseointegration in a human population.